A review of the Getting Real software development approach. (1st January 2012) - Sarja, Jari
The small US software developing company called 37signals is a significant phenomenon in many ways. The company has launched successful commercial web applications. The company has its own unique way of business thinking, and the people of the company do not have any growth target. The people of the company also have their own way of thinking about the software developing process. They have named it Getting Real. Getting Real is not described as a developing method; rather, it is a philosophy or approach behind the development activities. It has confluence with agile methods, but unlike agile methods, in Getting Real the nature of the final product is also strongly emphasised. The success of the company has proven that there is some effectiveness in the Getting Real approach. Therefore, the aim of this study is to find out whether the Getting Real approach can be supported by previous professional literature and scientific research.